2022
DOI: 10.1038/s42003-022-03309-9
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of STE20-type kinase STK25 in human aortic endothelial and smooth muscle cells is atheroprotective

Abstract: Recent studies highlight the importance of lipotoxic damage in aortic cells as the major pathogenetic contributor to atherosclerotic disease. Since the STE20-type kinase STK25 has been shown to exacerbate ectopic lipid storage and associated cell injury in several metabolic organs, we here investigate its role in the main cell types of vasculature. We depleted STK25 by small interfering RNA in human aortic endothelial and smooth muscle cells exposed to oleic acid and oxidized LDL. In both cell types, the silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…Previous research has demonstrated that ERS promotes the switching of SMCs from a contractile phenotype to a synthetic phenotype. 35 Zhao et al reported that ERS participates in the phenotypic transformation of VSMCs through the Notch pathway, 36 and Zhang et al determined that ERS promotes the phenotypic transformation of rat VSMCs through the PERK-eIF2a-ATF4-CHOP pathway, 20 , 37 in line with the present results. In our research, we demonstrated that 4-PBA reduced the stress level of the endoplasmic reticulum and reversed the phenotypic transition from the contractile phenotype to the synthetic phenotype.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has demonstrated that ERS promotes the switching of SMCs from a contractile phenotype to a synthetic phenotype. 35 Zhao et al reported that ERS participates in the phenotypic transformation of VSMCs through the Notch pathway, 36 and Zhang et al determined that ERS promotes the phenotypic transformation of rat VSMCs through the PERK-eIF2a-ATF4-CHOP pathway, 20 , 37 in line with the present results. In our research, we demonstrated that 4-PBA reduced the stress level of the endoplasmic reticulum and reversed the phenotypic transition from the contractile phenotype to the synthetic phenotype.…”
Section: Discussionsupporting
confidence: 90%
“…[80][81][82] Reciprocally, we show that diet-induced NASH is markedly aggravated in Stk25-overexpressing transgenic versus wild-type mice. [74,75] Of note, high-fat-fed Stk25 −/− mice also accumulate less ectopic fat in extrahepatic tissues such as skeletal muscle, kidney, and vascular wall, and have healthier adipose tissue, [82][83][84][85] which is accompanied by improved whole-body glucose tolerance and insulin sensitivity [82] compared with wild-type littermates.…”
Section: Silencing Of Stk 25 or Mst3 Hinders The De Velopment Of Nash...mentioning
confidence: 99%
“…In comparison to wild-type mice, STK25 −/− mice showed reduced atherosclerosis lesion area, decreased lipid accumulation, macrophage infiltration, and oxidative stress in aortic lesions [18]. The silencing of STK25 lowers oxidative and endoplasmic reticulum stress, decreases lipid accumulation, and inhibits the activation of inflammatory and fibrotic pathways in human aortic endothelial and smooth muscle cells exposed to oleic acid and oxidized LDL [19]. STK25 is also an MST kinase related to pancreas dysfunction [20].…”
Section: Stk25 and Energy Metabolismmentioning
confidence: 99%